Applied equine nutrition and training Equine NUtrition and TRAining COnference (ENUTRACO) 2011 - Lindner, Arno.; SpringerLink (Online service) (Wageningen : Wageningen Academic Publishers : Imprint: Wageningen Academic Publishers, 2012)
This book contains specialised information on the nutrition and training of the horse. Practical hints can be drawn from studies showing how apes indicate to us plants which have medicinal properties that can then be applied to equine treatment and also have an effect in nutraceuticals. Overviews are given on the potential of total mixed rations for the future of horse feeding and the practical feeding of obese horses and ponies. Nutrition considerations are given to avoid medical conditions. Methods used for performance diagnosis and training guidance of human athletes are applied here to equine management. In addition, training techniques which reduce the risk of back injury in the horse are explored and a review of the riders interaction with the horse is provided. Practical nutritional information acquired through research is applied to all aspects of managing endurance racehorses. Finally, expanded abstracts of original research are provided in very diverse fields of nutrition and training of horses. All those concerned with training, riding and feeding in the equine industry will benefit from the contents.
Editorial; A. Lindner -- Articles -- Practical news on equine nutrition for the breeder published in scientific literature between 2009-2011 -- The rider’s interaction with the horse -- Training techniques to reduce the risk of back injury -- Equine nutrition – clinical cases where nutrition is involved -- Feeding and training the endurance horse: how science can serve the practitioners -- How can we practically manage obese horses and ponies? -- Importance of the lactate parameter for performance diagnosis and for the regulation of training in top competition athletics and in recreational sports -- Performance diagnosis and training monitoring of human athletes in track & field running disciplines -- Practical news on advances in nutrition for performance horses and ponies between 2009-2011 -- Do animals use natural properties of plants to self-medicate? -- Feed supplements to maintain performance and health -- Will total mixed rations be the future of horse feeding? -- Expanded abstracts -- Effect of a complementary horse feed on nervous horse behaviour -- The effect of caecal pH on in vivo fibre digestibility in Norwegian trotter horses -- Effect of 5 week training period on the glycemic and insulinemic response to a cereal meal in Standardbreds -- The use of equine K4b during incremental field exercise tests in driven Standardbred trotters: a preliminary study -- The effects of a high starch, cereal-based diet compared to a low starch, fibre-based diet on reactivity in horses -- A marine mineral supplement for Aquacid™ -- High level endurance training: descriptive study based on the follow-up of the French team over seasons 2009 and 2010 -- Workload during an eventing competition.
Keywords: Life sciences; Life Sciences, general